Confirmation and Control of Triazine and 4-Hydroxyphenylpyruvate Dioxygenase-Inhibiting Herbicide-Resistant Palmer Amaranth (Amaranthus palmeri) in Nebraska. (March 2014) - Jhala, Amit J.; Sandell, Lowell D.; Rana, Neha; Kruger, Greg R.; Knezevic, Stevan Z.
Abstract : Palmer amaranth is a difficult-to-control broadleaf weed that infests corn and soybean fields in south-central and southwestern Nebraska and several other states in the United States. The objectives of this research were to confirm triazine and 4-hydroxyphenylpyruvate dioxygenase (HPPD)-inhibiting herbicide-resistant Palmer amaranth in Nebraska and to determine sensitivity and efficacy of POST-applied corn herbicides for control of resistant and susceptible Palmer amaranth biotypes. Seeds from a putative HPPD-resistant Palmer amaranth biotype from Fillmore County, NE were collected from a seed corn production field in fall 2010. The response of Palmer amaranth biotypes to 12 rates (0 to 12×) of mesotrione, tembotrione, topramezone, and atrazine was evaluated in a dose–response bioassay in a greenhouse. On the basis of the values at the 90% effective dose (ED90 ) level, the analysis showed a 4- to 23-fold resistance depending upon the type of HPPD-inhibiting herbicide being investigated and susceptible biotype used for comparison. This biotype also had a 9- to 14-fold level of resistance to atrazine applied POST. Results of a POST-applied herbicide efficacy study suggested a synergistic interaction between atrazine and HPPD-inhibiting herbicides that resulted in > 90% control of all Palmer amaranth biotypes. The resistant biotype had a reduced sensitivity to acetolactate synthase inhibiting herbicides (halosulfuron and primisulfuron), a photosystem-II inhibitor (bromoxynil), and a protoporphyrinogen oxidase inhibitor (fluthiacet-methyl). Palmer amaranth biotypes were effectively controlled (≥ 90%) with glyphosate, glufosinate, and dicamba, whereas 2, 4-D ester provided 81 to 83% control of the resistant biotype and > 90% control of both susceptible biotypes.